2021
DOI: 10.4067/s0718-58392021000300310
|View full text |Cite
|
Sign up to set email alerts
|

Response of green manure species and millet cultivars to different populations of Meloidogyne javanica

Abstract: The use of non-host cover crops is a key strategy for controlling root-knot nematodes in infested fields. However, pathogenicity of nematodes to cover crops may vary between populations and localities. This study assessed the response of green manure species and millet (Pennisetum glaucum (L.) R.Br.) cultivars to four populations of Meloidogyne javanica (denominated Mj-2, Mj-3, Mj-6 and Mj-7). Seedlings of radish (Raphanus sativus L.), pigeon pea (Cajanus cajan (L.) Huth) 'IAPAR 43', buckwheat (Fagopyrum escul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Most plant species studied here have previously shown potential to reduce Meloidogyne populations, including C. spectabilis (Miamoto et al, 2016), U. ruziziensis (Dias-Arieira et al, 2009), millet (Nascimento et al, 2020;Chidichima et al, 2021), and oat (Marini et al, 2016;Carraro-Lemes et al, 2020). The referred studies evaluated the efficiency of these plant species as cover crops, with or without green manure deposition, and, often, the effects of crops were attributed to their being antagonists or bad hosts to nematodes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Most plant species studied here have previously shown potential to reduce Meloidogyne populations, including C. spectabilis (Miamoto et al, 2016), U. ruziziensis (Dias-Arieira et al, 2009), millet (Nascimento et al, 2020;Chidichima et al, 2021), and oat (Marini et al, 2016;Carraro-Lemes et al, 2020). The referred studies evaluated the efficiency of these plant species as cover crops, with or without green manure deposition, and, often, the effects of crops were attributed to their being antagonists or bad hosts to nematodes.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, millet, C. spectabilis, U. ruziziensis, and white oat were shown to efficiently reduce populations of Meloidogyne spp. (Dias-Arieira et al, 2003;Miamoto et al, 2016;Carraro-Lemes et al, 2020;Chidichima et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(Melo et al, 2022). In a study assessing the response of green manure to M. javanica populations, Chidichima et al (2021) observed a reproduction factor (RF) of 2.94 to 53.46 on buckwheat, explaining the large nematode population in soybeans grown in succession to buckwheat.…”
Section: Meloidogyne Javanica Reproduction and Soybean Development In...mentioning
confidence: 99%
“…Cajanus cajan was shown to reduce M. javanica populations (Miamoto et al, 2016) and is used as a nematoderesistant standard, with reproduction factor (RF) values of 0.11 to 0.13 (Araújo Filho et al, 2010). Chidichima et al (2021), however, observed RF values of 0.58-2.99 that varyied according to M. javanica populations, suggesting a controversial antagonistic effect of C. cajan (Miamoto et al, 2016) attributed to the different behaviors of cultivars (Araújo Filho et al, 2010).…”
Section: Meloidogyne Javanica Reproduction and Soybean Development In...mentioning
confidence: 99%
“…compared to susceptible varieties. However, the effectiveness of this resistance can be associated with different factors, such as, pathogen population density, the state of homozygous and heterozygous of the resistance loci and soil temperature; temperatures greater than 28 °C result in a decrease of the effectiveness of Mi-1 gene (Özalp and Devran, 2018;Chidichima et al, 2021). High initial population densities not only affect crop yield and fruit quality, but interfere with the level of resistance conferred by the Mi-1 gene.…”
Section: Introductionmentioning
confidence: 99%